2004
DOI: 10.1159/000081114
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Iontophoresis of Insulin

Abstract: The delivery of large peptides through the skin poses a significant challenge, and various strategies are under active investigation for enhancing the transdermal permeation. For large peptides, it is difficult to achieve significant permeation using iontophoresis alone. Hence a combination of fatty acids with iontophoresis was hypothesized to result in higher enhancement than achieved with either of them alone. Saturated fatty acids and cis unsaturated fatty acids were studied in combination with iontophoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Moreover, both unsaturated fatty acids, oleic and linoleic acid produced permeation enhancement to the same extent for indomethacin [127] and arginine vasopressin [82], suggesting no effect of position and number of double bonds of unsaturated fatty acids on permeation enhancement. In contrast, increase in number of double bonds has been found to increase the permeation of some drugs like naloxone [128], alprazolam [129], paraaminobenzoic acid [47] and insulin [130]. In a recent study, the permeation of physostigmine ion paired with linoleic acid has been reported to be significantly lower than that ion paired with oleic acid.…”
Section: I) Fatty Acidsmentioning
confidence: 97%
“…Moreover, both unsaturated fatty acids, oleic and linoleic acid produced permeation enhancement to the same extent for indomethacin [127] and arginine vasopressin [82], suggesting no effect of position and number of double bonds of unsaturated fatty acids on permeation enhancement. In contrast, increase in number of double bonds has been found to increase the permeation of some drugs like naloxone [128], alprazolam [129], paraaminobenzoic acid [47] and insulin [130]. In a recent study, the permeation of physostigmine ion paired with linoleic acid has been reported to be significantly lower than that ion paired with oleic acid.…”
Section: I) Fatty Acidsmentioning
confidence: 97%
“…This state of oxidative stress can result in injury to all the important cellular components like proteins, DNA and membrane lipids which can cause cell death. In recent years, increasing experimental and clinical data has provided compelling evidences for the involvement of oxidative stress in large number of pathological states including carcinogenesis [27]. Oxidative stress however, is not always detrimental but selective oxidative stress sometimes is desirable and can be utilized therapeutically also.…”
Section: Anticancer Activity Of Prepared Compoundsmentioning
confidence: 99%
“…27,28) The absorption at 1740 cm Ϫ1 is from esterified carbonyl groups corresponding to endogenous skin lipids. 9) Figures 6a and b show the ATR-FTIR spectrum of rat skin treated with PBS solution (control) or 1.0% trypsin solution for 5 h. Compared with the control, some changes could be seen in the 1650 cm Ϫ1 region (amide I) and 1550 cm Ϫ1 region (amide II) in trypsin-treated skin samples (Fig. 6a).…”
Section: Atr-ftir Spectroscopymentioning
confidence: 99%
“…Most recent research has focused on the use of electrical energy to increase drug flux across the skin, including techniques such as iontophoresis, sonophoresis, electroporation, etc. [8][9][10] Unfortunately, the large, complex, and relatively uncharged insulin molecule still cannot across the intercellular lipid layer of the SC. The transport rate of hexameric insulin by iontophoresis across mouse skin has been low and variable.…”
mentioning
confidence: 99%